Sensitivity and Specificity of Portable Hearing Screening in Middle-Aged and Older Adults - Cardoso,Carolina Louise (2014)
Introduction  Hearing screening allows the identification of individuals with hearing loss. Aim  To determine the sensitivity and specificity of a portable hearing screening device in middle-aged and older adults using the manufacturer scoring and a scoring system proposed by the researchers. Methods  In this transversal study, participants underwent anamnesis, otoscopy, and hearing screening using portable equipment. After this, a pure tone audiometry was performed, with participants classified into two groups: with and without hearing loss. The sensitivity and specificity of the hearing screening were calculated for the right and left ears using two methods of interpretation: the original method recommended by the manufacturer (criteria 1) and the method proposed by researchers (criteria 2). Results  The sample consisted of 55 individuals, 83.6% (n = 46) of whom were women. Per criteria 1, the sensitivities were 26.3 (right ear) and 21.4% (left ear). The specificity was 100% for both ears. Using criteria 2, the sensitivity was 94.7 (right ear) and 100% (left ear). The specificity was 74.3 (right ear) and 65.9% (left ear). Conclusion  This study showed that the criteria proposed by the manufacturer presented low sensitivity in the hearing screening. The criteria proposed by the researchers to achieve a more efficient performance reached high and balanced values for sensitivity and specificity.